Artificial Intelligence, ChatGPT and Organizational Studies - Oliveira, Josiane Silva de; Barretto Souza Neves, Ianaira (Organizações & Sociedade, 2023)
The advancement of the use of Artificial intelligence in the scientific field, such as Connectedpapers and ChatGPT, has allowed us to reflect on how technological tools have become mediators and participants in the context of education and academia. In the field of organizational theories, despite the different perspectives on understanding the incorporation of AIs in academic practice, we highlight two challenges in our daily academic life. The first challenge refers to confronting the digital colonialism that AIs impose on us, considering that they constitute themselves through the reproduction of language models programmed in countries of the "global north” The second challenge concerns its unfoldings in the process of automation of academic writing in administration. We consider the need to reflect on how the uses of AIs can contemporarily reproduce our place in the field of science as one of scientific data extractivism, the limitation of the teaching of academic writing in administration as the reproduction of an "assisted programming" of hegemonic language models, and the possibilities of disentangling as a way of counteracting this dynamic of automation of article writing in administration.